2012
DOI: 10.1021/ef301633x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Anaerobic Digestion by the Addition of Paper Tube Residuals: Pretreatment, Stabilizing, and Synergetic Effects

Abstract: This study deals with the addition of paper tube residuals to a nitrogen-rich mixture of organic waste obtained from industrial and municipal activities. This nitrogen-rich mixture, called buffer tank substrate (BTS) in the following text, is used in a large-scale biogas plant. The effects were investigated in semi-continuous co-digestion processes, and variations in operational conditions were studied. The addition of paper tubes had stabilizing effects, prevented the failure of the process, and made it possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Codigestion is defined as the digestion of mixtures of at least two waste materials for improving AD efficiency. Many successful codigestions of substrates have increased methane potential substantially compared to the mono digestion of the substrates (González–Fernández et al 2011 ; Teghammar et al 2013 ). These study results clearly demonstrated and agreed with González–Fernández et al ( 2011 ) and Teghammar et al ( 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Codigestion is defined as the digestion of mixtures of at least two waste materials for improving AD efficiency. Many successful codigestions of substrates have increased methane potential substantially compared to the mono digestion of the substrates (González–Fernández et al 2011 ; Teghammar et al 2013 ). These study results clearly demonstrated and agreed with González–Fernández et al ( 2011 ) and Teghammar et al ( 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many successful codigestions of substrates have increased methane potential substantially compared to the mono digestion of the substrates (González–Fernández et al 2011 ; Teghammar et al 2013 ). These study results clearly demonstrated and agreed with González–Fernández et al ( 2011 ) and Teghammar et al ( 2013 ). Co-digestion of buffalo grass and buffalo dung produced higher accumulated biogas (15,521 ml) and rich methane content (71%) compared to mono digestion.…”
Section: Resultsmentioning
confidence: 99%
“…sewage sludge or protein-rich substrates have problems with a too low C/N ratio, which means a lack of carbohydrate-rich substrates. Addition of carbon-rich materials, such as lignocelluloses, was previously shown to both stabilize sensitive processes as well as result in good synergetic effects [39]. These synergetic effects have implied higher methane yields when a lignocellulosic-rich material (i.e., paper tube residuals) has been digested with nitrogen-rich substrate mixture compared to the expected methane production calculated from the methane potentials of the single substrate streams alone.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity and variability of biomass chemical structures, the optimal pretreatment method and conditions depend on the types of lignocellulose present. Several structural and compositional properties were found to have impacts on the biodegradability of lignocellulosic biomass, including cellulose crystallinity, accessible surface area, degree of cellulose polymerization, presence of lignin and hemicellulose, and degree of hemicellulose acetylation (Van Soest et al, 1991;Tang et al, 2011;Saha et al, 2013;Teghammar et al, 2013;Vázquez-Rowe et al, 2015;Tsai et al, 2016;Unpaprom et al, 2017;Vu et al, 2018;Tran et al, 2019;Manmai et al, 2020). The goal of pretreatment is to alter such properties to improve biomass amenity to enzymes and microbes.…”
Section: Resultsmentioning
confidence: 99%